Performance of Primary Health Centres in Dakshina Kannada District of Karnataka - Shriparasad H (KILA Journal of Local Governance, 2015)
In India Primary Health Centers (PHCs) are the cornerstone of rural health care; a first port of call for the sick and an effective referral system. It forms the first level of contact and link between individuals and the National Health System; bringing the health care delivery as close as possible to where people live and work. In this context analyzing the quality of performance of PHCs assumes to be highly prominent. The study considers the prime indicators such as Infrastructure of PHCs, General Medical/ Clinical care in PHCs.